A residual-energy-activated forwarding protocol using relay ordering and finite field network coding for multiple-source multiple-relay wireless sensor networks - Yulun Cheng; Longxiang Yang; Hongbo Zhu (International Journal of Distributed Sensor Networks)
Combining with finite field network coding, relay ordering is significant for the transmission reliability of multiple-source multiple-relay wireless sensor networks. However, it leads to severe energy consumption and is harmful to the lifetime of the network. To overcome the drawback of relay ordering and achieve desired trade-off between energy efficiency and transmission reliability, a residual energy-activated forwarding protocol is proposed in this article. In the protocol, by considering the unique characteristics of relay ordering–finite field network coding, a novel metric is proposed to jointly formulate both energy consumption and transmission reliability into one optimization problem. Based on this, the appropriate numbers of cooperative relays are selected to reduce energy consumption. Furthermore, by solving the proposed optimization problem in various cases, the optimization process is transferred to three sub-problems, and the corresponding strategy is developed to maximize the proposed metric accordingly. Extensive simulation results verify the superiority of the proposed protocol in both energy efficiency and transmission reliability.